Oral Cavity and Transmission of HIV: A Debatable Dilemma - Rawat, Shivani; Saxena, Susmita; Sharma, Preeti; Adhikari, Gautam (Journal of Orofacial Research, 2012)
Human immunodeficiency virus (HIV) is most commonly transmitted by sexual activity. HIV is found in blood and other body fluids, including semen, vaginal fluid and saliva. Spreadof the HIV from oral secretions of the millions of HIV viremic individuals, during kissing, dental treatment, biting is a very uncommon finding. The shedding of infected blood or exudates from the saliva of an infected individual usually contains only the noninfectious component of HIV and may also contain fragments or the entire noninfectious genome. The risk of HIV transmission via oral secretions is an issue of growing interest to the dental health professionals. The oral transmission of HIV remains a controversial issue and a cause of concern.